Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's proceed step-by-step to solve the given function [tex]\( y = 2 \times 2 - x - 1 \)[/tex].
1. First, evaluate the expression inside the function:
[tex]\[ y = 2 \times 2 - x - 1 \][/tex]
2. Start by calculating [tex]\( 2 \times 2 \)[/tex]:
[tex]\[ 2 \times 2 = 4 \][/tex]
3. Now substitute this result back into the equation:
[tex]\[ y = 4 - x - 1 \][/tex]
4. Next, simplify the expression by performing the subtraction [tex]\( 4 - 1 \)[/tex]:
[tex]\[ 4 - 1 = 3 \][/tex]
5. Now replace the simplified portion back into the equation:
[tex]\[ y = 3 - x \][/tex]
So, the simplified form of the function is:
[tex]\[ y = 3 - x \][/tex]
To find the values of [tex]\( y \)[/tex] for specific values of [tex]\( x \)[/tex], you can simply substitute those values of [tex]\( x \)[/tex] into the equation [tex]\( y = 3 - x \)[/tex].
For instance:
- If [tex]\( x = 0 \)[/tex], then [tex]\( y = 3 - 0 = 3 \)[/tex].
- If [tex]\( x = 1 \)[/tex], then [tex]\( y = 3 - 1 = 2 \)[/tex].
- If [tex]\( x = 2 \)[/tex], then [tex]\( y = 3 - 2 = 1 \)[/tex].
Thus, the function [tex]\( y = 3 - x \)[/tex] gives us a straight line when graphed and the values of [tex]\( y \)[/tex] for different [tex]\( x \)[/tex] can be determined as shown above.
1. First, evaluate the expression inside the function:
[tex]\[ y = 2 \times 2 - x - 1 \][/tex]
2. Start by calculating [tex]\( 2 \times 2 \)[/tex]:
[tex]\[ 2 \times 2 = 4 \][/tex]
3. Now substitute this result back into the equation:
[tex]\[ y = 4 - x - 1 \][/tex]
4. Next, simplify the expression by performing the subtraction [tex]\( 4 - 1 \)[/tex]:
[tex]\[ 4 - 1 = 3 \][/tex]
5. Now replace the simplified portion back into the equation:
[tex]\[ y = 3 - x \][/tex]
So, the simplified form of the function is:
[tex]\[ y = 3 - x \][/tex]
To find the values of [tex]\( y \)[/tex] for specific values of [tex]\( x \)[/tex], you can simply substitute those values of [tex]\( x \)[/tex] into the equation [tex]\( y = 3 - x \)[/tex].
For instance:
- If [tex]\( x = 0 \)[/tex], then [tex]\( y = 3 - 0 = 3 \)[/tex].
- If [tex]\( x = 1 \)[/tex], then [tex]\( y = 3 - 1 = 2 \)[/tex].
- If [tex]\( x = 2 \)[/tex], then [tex]\( y = 3 - 2 = 1 \)[/tex].
Thus, the function [tex]\( y = 3 - x \)[/tex] gives us a straight line when graphed and the values of [tex]\( y \)[/tex] for different [tex]\( x \)[/tex] can be determined as shown above.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.